The Influence of Organizational Culture and Work Environment on Job Satisfaction of Sharia Insurance Employees in Surabaya - Riduwan Riduwan (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
Employee satisfaction is an important factor that can influence organizational productivity and performance. This research aims to analyze the influence of organizational culture and work environment on employee satisfaction. The research method uses a quantitative approach with data collection techniques using questionnaires. The research sample was 50 employees of Sharia Insurance Companies in Surabaya. The data analysis technique uses multiple regression analysis and classical assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests. The results of the analysis show that both organizational culture and work environment have a significant positive influence partially and simultaneously on employee satisfaction